1980
DOI: 10.1161/01.str.11.5.517
|View full text |Cite
|
Sign up to set email alerts
|

Transient appearance of "no-reflow" phenomenon in Mongolian gerbils.

Abstract: We investigated the existence of the "no-reflow" phenomenon in focal cerebral ischemia. Regional cerebral blood flow was studied in Mongolian gerbils perfused with a carbon-black particle suspension after cerebral ischemia prior to decapitation and compared with 14C-antipyrine autoradiographic images. The correlation between the occurrence of the "no-reflow" phenomenon and systemic arterial blood pressure change was also examined. We found that the phenomenon was transient in character and that its manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 25 publications
(7 reference statements)
2
18
0
1
Order By: Relevance
“…Physiological values, MCA vascular diameter, and neurological function after sham surgery were similar in the transgenic and wild-type groups, indicating similar phenotypic baselines on which the effects of SAH were superimposed. Similarities of basilar (12) 15 (15) 12 (12) 39 (39) Wild-type SAH 7 (7-9) 7 (6-11) 10 (9-12) 23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) EC-SOD SAH 7 (6-8) 8 (8-11) 10 (9-11) 26 (23)(24)(25)(26)(27)(28)(29)(30) Values are median (IQR). *Range: 9ϭcomplete loss of function; 39ϭno deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological values, MCA vascular diameter, and neurological function after sham surgery were similar in the transgenic and wild-type groups, indicating similar phenotypic baselines on which the effects of SAH were superimposed. Similarities of basilar (12) 15 (15) 12 (12) 39 (39) Wild-type SAH 7 (7-9) 7 (6-11) 10 (9-12) 23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) EC-SOD SAH 7 (6-8) 8 (8-11) 10 (9-11) 26 (23)(24)(25)(26)(27)(28)(29)(30) Values are median (IQR). *Range: 9ϭcomplete loss of function; 39ϭno deficit.…”
Section: Discussionmentioning
confidence: 99%
“…10,26 Furthermore, perfusion fixation has become standard in the histological measurement of lumen diameters in rat and rabbit SAH models. 27,28 …”
Section: Cerebral Vascular Perfusionmentioning
confidence: 99%
“…Our findings are in line with those of several other studies that also reported transient no-reflow or impaired reflow after brief periods of cerebral ischemia. 21 - 26 Other studies did not show impairment of reperfusion, 27 -29 but these studies may have overlooked transient recirculation deficits because blood flow was measured intermittently.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of this phenomenon was confirmed in a variety of animal models of brain ischemia. [3][4][5][6] It was also shown in a variety of other organs, including skin, 7,8 skeletal muscle, 9 and the kidney. 10 -12 Kloner et al 13 sought to find out whether the no-reflow phenomenon would be observed in ischemic canine hearts and whether it was related to microvascular damage.…”
Section: Historical Perspectivementioning
confidence: 99%